Comparison of Conventional and Platelet‐Rich Plasma-Assisted Fat Grafting: A Systematic Review and Meta-analysis. Issue 11 (November 2021) - Wu, Mengfan; Karvar, Mehran; Liu, Qinxin; Orgill, Dennis P.; Panayi, Adriana C.
Abstract: Background: Autologous fat grafting (FG) is a popular technique for soft-tissue augmentation, but the fat survival rate is unpredictable. Platelet-rich plasma (PRP) has emerged as an adjuvant to enhance fat graft survival. Objectives: This literature review and meta-analysis aimed to investigate the effect of PRP on the survival rate of fat grafting. Methods: A comprehensive systematic literature search was done to identify clinical studies on PRP and fat cotransplantation in PubMed, Cochrane Library, Web of Science, and EMBASE databases up to May 2020. The reference lists of selected articles were reviewed to identify any additional related articles. A meta-analysis was conducted to compare PRP + FG and conventional FG in terms of fat graft survival rate, patient satisfaction rate, and recovery time after surgery. Results: Eleven studies consisting of 1125 patients were analyzed. Patients were followed up from 3 to 24 months post-FG. The fat survival rate varied from 20.5% to 54.8% in FG alone and from 24.1% to 89.2% in the PRP + FG groups. The survival rate was significantly higher and recovery time was significantly lower in the PRP + FG group than in the FG alone group. However, there was no significant difference in the patient satisfaction rate between the groups. Conclusions: This study demonstrates that PRP-enhanced fat transplantation has better efficacy than conventional fat grafting. Further studies are required to provide the optimum concentration of PRP and the long-term efficacy of the technique. There is not enough evidence to compare the rate of complications with PRP and fat cotransplantation and conventional fat grafting.